Compromised Medical Products A Scoping review of Quality, Safety and Efficacy Concerns - Dewan, Shailee; Naik, Nikhil Narayan; Artham, Pranagini; Janodia, Manthan Dilipkumar; Muragundi, Pradeep Manohar (Indian Journal of Pharmaceutical Education and Research, 2026)
Background: In 2011, the World Health Organization (WHO) coined the term substandard/ spurious/falsely labelled/falsified/counterfeit (SSFFC) to describe medical products that compromise quality, safety, and efficacy. Despite its broad usage, the term 'SSFFC' was not sufficient to differentiate between the various categories of illicit medicines, each of which requires distinct regulatory responses. In 2017, the WHO took a significant step by rationalizing the terminology, promoting transparency, and clearly distinguishing between substandard and counterfeit medicines. The rationality behind this study was to explore the various dimensions of SSFFC drug products from definitions to their global impact posed by these hazardous products. Materials and Methods: Databases like Scopus, Medline, PubMed, and Embase, were systematically searched for publications between October 2011 and January 2023. To ensure the results were appropriate, WHO alert data from 2019 to December 2024 was also reviewed. Using Covidence, descriptive analysis and narrative synthesis was performed. Out of 6424 of total articles, 4522 articles were assessed for eligibility after 1902 duplicates were eliminated out. For data extraction, 60 articles in total were selected. Results: The findings from this study provide a comprehensive compilation of definitions and characterizations of SSFFC medical products across different sources. The review also explored WHO global alerts, which provided the affected essential drugs in low- and middle-income countries, leading to significant health consequence in developing regions. Conclusion: The findings highlight the pressing need for stronger regulatory frameworks and international cooperation to combat the spread of SSFFC products. Additionally, the study's review of WHO global alerts emphasizes the urgency of addressing the health consequences posed by these products. It also provides recommendations for future research, emphasizing the need to explore regulatory actions for SSFFC medical products and to strengthen global efforts to protect public health.
Keywords: Substandard; Spurious; Falsified; Falsely labelled; Counterfeit.